I am a man! : race, manhood, and the civil rights movement - Estes, Steve (UNC Press law publications., 2005)
This explores key groups, leaders and events in the civil rights movement to understand how activists used race and manhood to articulate their visions of what American society should be. He demonstrates that both segregationists and civil rights activists harnessed masculinist rhetoric, tapping into assumptions about race, gender, and sexuality.